Efektivitas Program Kuliah Kerja Nyata (KKN) Universitas Abdurrab dalam Meningkatkan Literasi, Kesehatan, dan Kesadaran Sosial Masyarakat Kelurahan Tobekgodang - Yulnefia Yulnefia; Cindi Yulia; Anjani Syahadry; Salamatul Aini; Nur Hafizah; Sri Lestari; Tirta Aprilia; Verga Septiana; Devi Darman Putra; Aghina Humaira; Nabil Durratul Aini (Jurnal Pengabdian Masyarakat, 2025)
Community Service (KKN) is a form of community service activities carried out by students by applying the knowledge and skills that have been acquired during lectures into real practice in the field. The Abdurrab University KKN is carried out through 13 work programs involving elementary, junior high, high school, vocational school students, and the community in Tobekgodang Village. This study uses a quantitative approach with a pretest-posttest quasi-experimental design, where the research instrument is in the form of a Likert scale questionnaire, and the data is analyzed using the paired samples t-test. The results of the study showed a significant increase in all activity programs. For example, in the Maghrib Mengaji program, the average score increased from 15.8 to 20.3, while in Clean and Healthy Living Behavior (PHBS) and Anti-Bullying counseling, the score increased from 14.1 to 18.2. These results show that the implementation of KKN is not only a means of student service, but also effective in improving literacy, social awareness, participant character, and the quality of life of the community in a sustainable manner in various aspects of life.